Dynamic Characterization and Constitutive Modelling of ARMSTAL 500 Steel - Djalel Eddine TRIA (Wojskowa Akademia Techniczna, 2015)
The behaviour of a high strength steel (ARMSTAL 500) has been investigated using a combination of quasistatic and dynamic tests for a wide strain-rate range 1·10-4 – 3·10+3 s-1. A uniaxial testing machine and a Split Hopkinson Pressure Bar (SHPB) have been used under well controlled testing conditions. Next, the effect of the strain hardening, the strain rate hardening, loading history and stress triaxiality on the strength and ductility of the material has been studied. The present work also describes constitutive and damage models and their implementation available in the nonlinear finite element code LS DYNA. Calibration of constitutive model parameters and damage criteria is most often accomplished via regression techniques applied to laboratory data. A 3D numerical simulation of perforation of ARMSTAL 500 plates with 7.62 × 51 mm AP projectile were carried out with detailed models of target and compared with experiment in order to validate the calibrated models. As it will be shown, ARMSTAL 500 steel is a high strength steel with modest strain-rate sensitivity. The study indicates that the penetration depth can be predicted quantitatively and qualitatively with MJC hardening parameters calibrated from compression tests.The Modified Johnson–Cook constitutive model with Cockcroft and Latham failure model can predict the projectile residual speed and the fragmentation process followed very closely by MJC failure criteria.
Keywords: Modelowanie zjawisk balistyki końcowej